Treatment Patterns, Adverse Events, and Clinical Outcomes with Steroidal Mineralocorticoid Receptor Antagonists: A Retrospective Analysis of Administrative Claims Data (RELICS) - Richard EL; Desai NR; Willey VJ; Gay A; Scott C; Folkerts K; Pessina E; Singh R; Teng CC; Oberprieler NG (Pragmatic and Observational Research)
Emma L Richard,1 Nihar R Desai,2 Vincent J Willey,1 Alain Gay,3 Charlie Scott,4 Kerstin Folkerts,5 Elena Pessina,6 Rakesh Singh,7 Chia-Chen Teng,1 Nikolaus G Oberprieler8 1Health Economics and Outcomes Research, Carelon Research, Wilmington, DE, USA; 2Department of Cardiovascular Medicine, Yale School of Medicine, New Haven, CT, USA; 3Clario, Philadelphia, PA, USA; 4Clinical Statistics and Analytics, Bayer US LLC, Whippany, New Jersey USA; 5Health Economics and Outcomes Research, Bayer AG, Wuppertal, Germany; 6Integrated Evidence Generation, Bayer S.p.A., Milan, Italy; 7Value, Evidence, and Outcomes, Eli Lilly and Co, Indianapolis, IN, USA; 8Integrated Evidence Generation, Bayer AS, Oslo, NorwayCorrespondence: Emma L Richard, Research Scientist, Carelon Research, HEOR, 123 Justison Street, Wilmington, DE, 19801, USA, Email emma.richard@carelon.comPurpose: This study aimed to describe the characteristics, treatment patterns, adverse events (AEs), and clinical outcomes of patients starting steroidal mineralocorticoid receptor antagonists (sMRAs) in real-world settings.Methods: The RELICS study, complementing the survey-based RELICS-PS study, was a retrospective cohort study conducted using the Healthcare Integrated Research Database (HIRD®), a single-payer healthcare database with medical and pharmacy claims from health insurance plans across the United States. A cohort of adults initiating sMRAs from January 2016 to June 2021 was divided into six subgroups: three mutually exclusive heart failure (HF) subgroups, two mutually exclusive chronic kidney disease (CKD) subgroups, and “all other patients” subgroup, which included those without documented HF or CKD. Outcomes assessed from the first sMRA fill until death, health-plan disenrollment, or June 2022 (whichever came first) included analysis of treatment patterns, AEs, and clinical outcomes. Factors associated with sMRA discontinuation were evaluated with multivariate logistic regression.Results: Of the 224,100 sMRA initiators identified, 76.4% did not have documented HF or CKD (ie, “all other patients” subgroup). This subgroup was younger and primarily female. Across all initiators, 72.3% were nonadherent, and 73.0% discontinued treatment within a median of 90 days of initiation. Of these discontinuers, 44.2% restarted treatment within a median of 91 days of discontinuation. Factors decreasing odds of discontinuation across most subgroups included a higher comorbidity burden, use of other cardiovascular medications, and cardiologist prescribing. These findings were consistent across subgroups. AEs and clinical outcomes varied across subgroups in line with baseline comorbidity profiles. Patients with a higher comorbidity burden, such as those with both CKD and T2D rather than CKD alone, experienced worse outcomes.Conclusion: High rates of treatment discontinuation and subsequent restart were observed across all subgroups, implying fluctuating sMRA use. However, heightened cardiovascular risk may decrease the odds of discontinuation.Keywords: steroidal mineralocorticoid receptor antagonists, treatment patterns, adverse events, clinical outcomes, real-world data, administrative claims